2016
DOI: 10.1111/aab.12296
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility and tolerance in hybrid and pure-line rice varieties to herbivore attack: biomass partitioning and resource-based compensation in response to damage

Abstract: Hybrid rice has been noted for its susceptibility to insects and diseases compared to pure-line (conventional) rice varieties. We investigated herbivory by Nilaparvata lugens, Sogatella furcifera and Scirpophaga incertulas on replicated three-line hybrid sets (parental and hybrid lines) in field and greenhouse experiments. In a field experiment, caterpillar densities and stemborer damage was similar among hybrid and parental lines. In field and greenhouse experiments, the cytoplasmic male sterile (CMS)-lines a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
66
2
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(71 citation statements)
references
References 20 publications
2
66
2
1
Order By: Relevance
“…However, they also become notably more attractive to pests and more susceptible to a variety of diseases (Horgan and Crisol, 2013;Horgan et al, 2016a;Hu et al, 2016). Field and laboratory studies have indicated higher levels of damage from insects, snails and weeds to rice produced under high nitrogen conditions (Eggum and Juliano, 1973;Ampong-Nyarko and Datta, 1993;Hu et al, 2016).…”
Section: Increasing Fertilizer Usementioning
confidence: 99%
See 4 more Smart Citations
“…However, they also become notably more attractive to pests and more susceptible to a variety of diseases (Horgan and Crisol, 2013;Horgan et al, 2016a;Hu et al, 2016). Field and laboratory studies have indicated higher levels of damage from insects, snails and weeds to rice produced under high nitrogen conditions (Eggum and Juliano, 1973;Ampong-Nyarko and Datta, 1993;Hu et al, 2016).…”
Section: Increasing Fertilizer Usementioning
confidence: 99%
“…Rice plants under high nitrogen are predicted to better tolerate damage (can compensate for biomass loss) depending on the nature of the attacking herbivore or parasite (Horgan et al, 2016a;Prot et al, 1994). For example, yield losses to rice from certain insect herbivores can be avoided by treating affected plants with high nitrogen (Jiang and Cheng, 2003;Inthavong et al, 2004).…”
Section: Increasing Fertilizer Usementioning
confidence: 99%
See 3 more Smart Citations